THE ROLE OF CHINESE CULTURE AND ITS IMPACT ON THE CIVILIZATION - Tulanovna, Burkhanova Sabo (PT. Antis International Publisher, 2024)
Objective: This study examines the emergence and development of art in ancient Egypt, a process spanning over 4,500 years, and its profound impact on both the civilization and the broader history of human artistic expression. Method: The research utilizes a historical and comparative approach, analyzing key monuments and artistic works from various periods in ancient Egypt, alongside relevant archaeological and textual evidence, to assess their cultural significance. Results: Egyptian art represents a critical stage in the evolution of human creativity, characterized by monumental architecture, sculpture, and painting, which not only served religious and funerary purposes but also conveyed deep insights into the Egyptian worldview, emotions, and spiritual beliefs. Novelty: This article highlights the unique role of Egyptian art in shaping the human experience, as it was among the first to express complex human feelings and individual identities within a broader cultural framework. The study underscores the far-reaching influence of Egyptian art on subsequent civilizations, contributing to the cultural and artistic development of the ancient world.